Thrombin as a multi-functional enzyme - Siller-Matula, Jolanta M.; Schwameis, Michael; Blann, Andrew; Mannhalter, Christine; Jilma, Bernd (Thrombosis and Haemostasis, 2011)
Thrombin is the central protease in the coagulation cascade and one of the most extensively studied of all enzymes. In addition to its recognised role in the coagulation cascade and haemostasis, thrombin is known to have multiple pleiotropic effects, which mostly have been shown only in in vitro studies: it plays a role in inflammation and cellular proliferation and displays a mitogen activity on smooth muscle cells and endothelial cells, predominantly by activation of angiogenesis. In vivo, thrombin effects were examined in animal models of intravenous or intraarterial thrombin infusion. An extensive literature search regarding in vivo data showed that i) thrombin administered as a bolus causes microembolism, ii) thrombin infused slowly at steady-state conditions (up to 1.6 U/kg/min) leads to bleeds but not to intravascular clotting, iii) large quantity of thrombin infused at low rates (0.05 U/kg/min) does not have any measurable effect, and iv) thrombin increases vascular permeability leading to tissue damage. Although several decades of research on thrombin functions have provided a framework for understanding the biology of thrombin, animal and human studies with use of newer laboratory techniques are still needed to confirm the pleiotropic thrombin functions shown in in vitro studies.Focus on in vitro and in vivo effects
Keywords: Thrombin; animal studies; coagulation; pleiotropic; PAR